2016
DOI: 10.1681/asn.2016040433
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter Study of the Predictive Value of Crescents in IgA Nephropathy

Abstract: The Oxford Classification of IgA nephropathy does not account for glomerular crescents. However, studies that reported no independent predictive role of crescents on renal outcomes excluded individuals with severe renal insufficiency. In a large IgA nephropathy cohort pooled from four retrospective studies, we addressed crescents as a predictor of renal outcomes and determined whether the fraction of crescent-containing glomeruli associates with survival from either a $50% decline in eGFR or ESRD (combined eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
213
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 251 publications
(236 citation statements)
references
References 26 publications
16
213
2
5
Order By: Relevance
“…Crescents were also found to be predictive of poor renal outcomes in several other studies including patients with eGFR <30 ml/min 12,13 31 . Therefore, we propose that the Oxford classification should now involve five components, MEST-C rather than MEST.…”
Section: Crescentsmentioning
confidence: 67%
See 1 more Smart Citation
“…Crescents were also found to be predictive of poor renal outcomes in several other studies including patients with eGFR <30 ml/min 12,13 31 . Therefore, we propose that the Oxford classification should now involve five components, MEST-C rather than MEST.…”
Section: Crescentsmentioning
confidence: 67%
“…Since cases of Henoch-Schönlein purpura nephritis were excluded from the recent study of crescents in IgAN 31 , we recommend the MEST-C score not to be applied to cases of Henoch-Schönlein purpura nephritis yet.…”
Section: The Revised Mest-c Scorementioning
confidence: 99%
“…A recent large IgAN cohorts revealed that crescents predicted a higher risk of 50% decline in eGFR or ESRD in patients without receiving immunosuppression [29]. Moreover, having crescents in at least one fourth of glomeruli independently related with a combined event in patients, no matter receiving immunosuppression or not.…”
Section: Resultsmentioning
confidence: 99%
“…The Oxford classification was proposed by the Working Group of the International IgA Nephropathy Network and it has gained worldwide acceptance [25-27]. We compared the renal histology of C. rectus -positive and -negative groups of IgAN patients using the Oxford classification in a blind test.…”
Section: Methodsmentioning
confidence: 99%